A systematic scoping review and textual narrative synthesis of the qualitative evidence related to adolescent idiopathic scoliosis. (May 2022) - Essex, Ryan; Bruce, Gemma; Dibley, Molly; Newton, Paul; Thompson, Trevor; Swaine, Ian; Dibley, Lesley
Abstract: Introduction: This systematic scoping review sought to summarise and synthesise the qualitative evidence on adolescent idiopathic scoliosis (AIS) to understand the experiences of AIS, and of its diagnosis and treatment, and effective coping strategies to inform directions for future research. Method: A systematic scoping review and textual narrative synthesis was undertaken. Qualitative or mixed-methods studies with extractable qualitative data were included if participants had AIS, and patient or patient relative perspectives about AIS or its treatment were reported. Results: Fifteen papers were included. These suggested that AIS can influence self-image and perceptions of appearance and can cause those with the condition to reluctantly adjust parts of their lives and avoid some activities. The diagnosis and treatment of AIS is a major event and is often accompanied by shock, uncertainty, and anxiety. Whilst some find surgery stressful, others were relieved to have the surgery, and were generally happy with the outcome. Immediate family members may be distressed by the diagnosis and treatment of AIS. Discussion: AIS diagnosis and treatment has a substantial impact on adolescents and their families that is only addressed in part in this review. There is a pressing need for more qualitative research to understand needs, perspectives and experiences of adolescents with AIS and their families from the point of diagnosis, throughout treatment, and in the longer-term.